2004
DOI: 10.1038/sj.cdd.4401391
|View full text |Cite
|
Sign up to set email alerts
|

Human death effector domain-associated factor interacts with the viral apoptosis agonist Apoptin and exerts tumor-preferential cell killing

Abstract: Apoptin, a protein from chicken anemia virus without an apparent cellular homologue, can induce apoptosis in mammalian cells. Its cytotoxicity is limited to transformed or tumor cells, making Apoptin a highly interesting candidate for cancer therapy. To elucidate Apoptin's mechanism of action, we have searched for binding partners in the human proteome. Here, we report that Apoptin interacts with DEDAF, a protein previously found to associate with death effector domain (DED)-containing pro-apoptotic proteins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 32 publications
0
72
0
Order By: Relevance
“…Only one tumour-suppressor gene, RYBP, was present in this region. RYBP (RING1 and YY1 binding protein, also known as DEDAF) functions as a repressor of E4TF1 and induces apoptosis in tumour cells (Danen-van Oorschot et al 2004). The preferential tumour-killing activity of RYBP has made it a promising target for cancer therapy (Novak & Phillips 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Only one tumour-suppressor gene, RYBP, was present in this region. RYBP (RING1 and YY1 binding protein, also known as DEDAF) functions as a repressor of E4TF1 and induces apoptosis in tumour cells (Danen-van Oorschot et al 2004). The preferential tumour-killing activity of RYBP has made it a promising target for cancer therapy (Novak & Phillips 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, high levels of dRYBP expression induce apoptosis in all the imaginal discs studied (Figure 1). In transfection experiments, murine and human RYBP/DEDAF proteins have been shown to have the ability to specifically kill mammalian tumor cells while leaving normal cells unaffected [19,20]. We have shown that the induction of apoptosis in Drosophila does not require the apoptotic cell to be in the transformed state, indicating that this may be a useful system to study the mechanisms controlling the tumor-specific cell killing.…”
Section: High Levels Of Exogenous Drybp Induce Apoptosismentioning
confidence: 94%
“…Furthermore, the RYBP protein has been found to interact with Apoptin, a protein known to be active in killing tumor cells [20]. As induction of apoptosis is a common mechanism underlying cancer therapy, understanding the mechanisms controlling tumor cell-specific killing may facilitate the development of improved therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray structure of the monomers of C-RING1B resembles that of a ubiquitin module, and it serves to interact with CBX proteins (18). Furthermore, we have also shown that C-RING1B is capable of interacting with RING1 and YY1 binding protein (RYBP) (19,20), which is a highly basic, oligomeric, intrinsically disordered protein (IDP) that interacts with DNA (19) and other proteins involved in apoptosis (21)(22)(23). The CBX proteins binding to C-RING1B undergo a tightening in their structures (24), and their presence hampers RYBP binding (25).…”
mentioning
confidence: 85%